Archaeal hyperthermostable mannitol dehydrogenases: A promising industrial enzymes for d-mannitol synthesis. (November 2020) - Koko, Marwa Yagoub Farag; Mu, Wanmeng; Hassanin, Hinawi Abdo Mustafa; Zhang, Shuang; Lu, Han; Mohammed, Jalaleldeen Khaleel; Hussain, Muhammad; Baokun, Qi; Yang, Li
Graphical abstract: The proposed pathways of D-mannitol production via hyperthermophilic archaeal. Highlights: Purified MtDH is an exceptional promoter for mannitol synthesis. MtDH with unique properties is proposed as an industrial enzyme. MtDH is a promised biocatalyst to fulfill the gab in food and medical applications. Abstract: Recently, the term healthy lifestyle connected to low-calorie diets, although it is not possible to get rid of added sugars as a source of energy, despite the close relation of added sugars to some diseases such as obesity, diabetes, etc. As a result, the sweetener market has flourished, which has led to increased demand for natural sweeteners such as polyols, including d -mannitol. Various methods have been developed to produce d -mannitol to achieve high productivity and low cost. In particular, metabolic engineering for d -mannitol considers one of the most promising approaches for d -mannitol production on the industrial scale. To date, the chemical process is not ideal for large-scale production because of its multistep mechanism involving hydrogenation and high cost. In this review, we highlight and present a comparative evaluation of the biochemical parameters that affecting d -mannitol synthesis from Thermotoga neapolitana and Thermotoga maritima mannitol dehydrogenase (MtDH) as a potential contribution for d -mannitol bio-synthesis. These species were selected because purified mannitol dehydrogenases from both strains have been reported to produce d -mannitol with no sorbitol formation under temperatures (90–120 °C).